Música e poesia : Senhas de Adriana Calcanhotto - Dumont, Mirian Lesbão (2013)
This dissertation presents a study about Adriana Calcanhotto’s songs. It brings out the connection of music and literature. The selected corpus comprises songs and poems composed end musiced by her. In the first stage of the study, the intersection between the two forms of art was done. The historical recollection of these two forms of art was also presented. At the interface, the musical rhythms as unfolding of some songs and poems were observed. In these dimensions, the lyrics and musical arrangements of the urban landscape were revealed as the theme; the intertextuality as precursor element of the song, referred to the dialogism discoursed on music production of Calcanhotto, Caetano Veloso and the modernists Oswald and Mário de Andrade. The meta language, concerning the reflections on the artistic singer’s production that give us a dimension of changes in the urban and artistic contexts as well as in the literature and music was also studied.